Implementasi Communicative Language Teaching dalam Pembelajaran Maharah Kalam di Era Media Sosial: Analisis Budaya Komunikasi Digital Generasi Z - Nopandri, Ramdani; Lukluk Isnaini, Rohmatun; Fatimah Zahrah; Diva Prima Aisyahrani, Diva; Rahmadani5, Mely (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2026)
This study analyzes the implementation of Communicative Language Teaching (CLT) in māhārah kalām (Arabic speaking skills) instruction at SMK Ulil Albab NW Gegek, involving 28 Grade XI students and one Arabic language teacher. The study employed a qualitative descriptive-analytical design with data collected over eight classroom observations through participatory observation, semi-structured interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model with triangulation of sources and techniques to ensure credibility. Findings indicate that CLT significantly transformed classroom interaction patterns from form-oriented to meaning-oriented instruction, increasing both the frequency and distribution of oral participation. Communicative activities such as contextual dialogue, group discussion, role play, and social simulation increased student speaking confidence and fluency. However, grammatical accuracy has not yet developed uniformly across learners, reflecting the typical fluency-accuracy trade-off in early CLT implementation. The results reinforce the relevance of communicative competence in Arabic language instruction at the vocational level, demonstrating that contextual communicative practice aligned with Generation Z communication culture can optimize māhārah kalām development. This study contributes a novel analysis of CLT implementation in the SMK context by explicitly linking communicative pedagogy with the digital communication culture of Generation Z students.